Perceived Stress and Daily Well-Being During the COVID-19 Outbreak: The Moderating Role of Age - Jiang, Da (Frontiers in Psychology, 2020)
Objectives Older adults are considered one of the most vulnerable groups to COVID-19. However, previous studies on emotion and aging have found that older adults report better well-being than younger adults in global survey and daily report. To better understand older adults’ well-being during the COVID-19 outbreak, we examined age differences in daily affective experiences in this study. Method Two hundred and thirty-one participants from mainland China aged 18 to 85 were recruited to participate in the 14-day daily diary study, after a pretest. Their trait affect and demographic information were measured in the pretest. Their daily affect and stress levels were measured in the daily assessments. Results We found that older adults reported lower perceived stress related to COVID-19 in daily life, compared to younger adults. The negative relationship between daily perceived stress and high arousal positive affect and the positive relationship between daily perceived stress and high arousal negative affect was weaker in older than younger adults. Discussion These results provide initial evidence of daily affective well-being across different age groups in adulthood during the COVID-19 outbreak. Such information is important for developing interventions to promote better well-being during the COVID-19 outbreak.